OPTIMIZED HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY-FLUORESCENCE DETECTION METHOD FOR THE MEASUREMENT OF GLYCINE, PROLINE, AND HYDROXYPROLINE CONCENTRATIONS IN PORCINE GELATIN - Ekasary, Aryaty; ., Harmita; Maggadani, Baitha Palanggatan (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study is to develop an optimized method for glycine, proline, and hydroxyproline content quantitation in porcine skin gelatin. Methods: Gelatin was isolated from porcine skin by hydrolysis for 24 h in 0.5 M acetic acid, heating in distilled water at 55°C for 3 h, and drying at 60°C. The extract was evaluated by organoleptic tests, Fourier-transform infrared spectroscopy, moisture assay, ash assay, and viscosity test. Gelatin amino acids were derivatized using 9-fluorenylmethylchloroformate-chloride and measured by high-performance liquid chromatography (HPLC) with fluorescence detection using a C18 column after the optimization of the mobile phase composition, flow rate, and detection wavelengths. Results: The optimized parameters for the quantitation of glycine, proline, and hydroxyproline by HPLC with fluorescence detection were as follows: Excitation wavelength, 265 nm; emission wavelength, 320 nm; mobile phase composition acetic buffer: acetonitrile, 55:45; and flow rate, 0.8 mL/min. The average proportional amino acid contents were 28.57±0.74%, 19.24±0.48%, and 2.89±0.33% for glycine, proline, and hydroxyproline, respectively. Conclusion: This method allows for sensitive and accurate quantitation of glycine, proline, and hydroxyproline in porcine skin gelatin samples for quality control and source determination.